2019
DOI: 10.3390/catal9010096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mono-, Di-, and Triethylene Glycol on the Activity of Phosphate-Doped NiMo/Al2O3 Hydrotreating Catalysts

Abstract: The effect of glycols on the catalytic properties of phosphate-doped NiMo/Al2O3 catalysts in the hydrotreating of straight-run gas oil (SRGO) was studied. The NiMo(P)/Al2O3 catalysts were prepared using ethylene glycol (EG), diethylene glycol (DEG), and triethylene glycol (TEG) as additives. The organic agent was introduced into the aqueous impregnation solution obtained by the dissolving of MoO3 in H3PO4 solution, followed by Ni(OH)2 addition. The Raman and UV–Vis studies show that the impregnation solution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The fact that ethylene glycol stabilizes molybdenum complexes has been previously reported in the literature [ 30 ], and is likely due to chelation between the small molecule diol and molybdenum that retards undesired side reactivity. Of note, other aliphatic alcohols, including glycerol and 3-propane diol, were less effective at stabilizing the molybdenum reagent, as were supramolecular additives with multiple hydroxyl moieties, including α, β, and γ-cyclodextrin.…”
Section: Resultsmentioning
confidence: 83%
“…The fact that ethylene glycol stabilizes molybdenum complexes has been previously reported in the literature [ 30 ], and is likely due to chelation between the small molecule diol and molybdenum that retards undesired side reactivity. Of note, other aliphatic alcohols, including glycerol and 3-propane diol, were less effective at stabilizing the molybdenum reagent, as were supramolecular additives with multiple hydroxyl moieties, including α, β, and γ-cyclodextrin.…”
Section: Resultsmentioning
confidence: 83%
“…It is well known that DEG does not form complex compounds with Co or Mo in solution. 24 However, a positive effect of the glycols on the activity of CoMoP catalysts based on γ-alumina was established. 64 It is assumed that the positive effect of glycols may be due to the fact that they interact with coordinatively unsaturated Al 3+ sites on the surface of alumina.…”
Section: Resultsmentioning
confidence: 99%
“…41 The use of DEG as an organic additive does not lead to the formation of Co or Mo complex compounds in the solution. 24 The evaluation of the morphology and textural characteristics of the obtained CoMoS catalysts showed that the use of various organic additives had an insignificant effect. The sulfide particles with a slab length of 2.0−3.0 nm are predominant in the CoMoS samples prepared with CA and NTA, whereas the CoMoS sample prepared using DEG has a slightly higher slab length (2.0−3.3 nm).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations